Patients with pure dermatomyositis/polymyositis and anti-PM/Scl autoantibody resembling anti-synthetase syndrome - Alves,Samara Pereira (2018)
OBJECTIVE: The anti-PM/Scl autoantibody has been described in patients with scleromyositis. However, there are scant studies evaluating its prevalence and reactivity in dermatomyositis and polymyositis. METHOD: A cross-sectional, single center study evaluating the anti-PM/Scl autoantibody in 85 dermatomyositis and 32 polymyositis patients, without overlapping syndrome, was conducted between 2000 and 2016. Clinical data and complementary examinations were reviewed from electronic medical records with pre-parameterized information. RESULTS: The mean age of dermatomyositis and polymyositis patients was 41.1 and 42.8 years, respectively. The presence of anti-PM/Scl was observed in 5 (5.9%) dermatomyositis and 2 (6.3%) polymyositis patients. Two of these patients also had the anti-Ku antibody. The relevant clinical manifestations of these 7 patients were constitutional symptoms (100% of cases), muscular (100%), pulmonary (85.7%) and joint (71.4%) involvement, "mechanic hands" (85.7%), Raynaud phenomenon (85.7%) and plantar hyperkeratosis (85.7%). The 7 patients had relapses of disease activity, but at conclusion of the present study, 5 had complete clinical response and 2 complete remission of the disease. CONCLUSION: There is a low frequency of the anti-PM/Scl autoantibody in dermatomyositis and polymyositis patients. In addition, patients with this autoantibody exhibit a similar pattern of manifestations to that of antisynthetase syndrome.